Developing an Architectural Spatial Integration Framework for Sustainable Waste Management Education Facilities - Arya Sagara Dwi Indrawanto; Luhur Sapto Pamungkas; Endah Tisnawati (International Journal of Science and Environment (IJSE), 2026)
The growing adoption of Waste-to-Energy facilities requires an architectural approach capable of integrating industrial operations, environmental education, and sustainable waste management within a coherent spatial system. However, existing studies primarily emphasize technological optimization, industrial building performance, or educational environments independently, leaving limited attention to architectural spatial integration as a design foundation. This study aims to develop an Architectural Spatial Integration Framework to support the design of Sustainable Waste Management Education Facilities. A Design-Based Research approach was employed through the synthesis of scientific literature, policy reviews, architectural precedent studies, and comparative analysis to identify transferable spatial design principles. The proposed framework consists of four integrated components, namely Spatial Organization Integration, Functional Integration, Environmental Integration, and Architectural Integration, which are translated into architectural design parameters including zoning, circulation, spatial hierarchy, building form, environmental systems, visual connectivity, and educational spaces. The framework is subsequently implemented through a conceptual architectural model demonstrating how industrial operations, visitor experiences, environmental learning, and sustainable building strategies can be integrated into a coherent spatial configuration. The findings establish Architectural Spatial Integration as the principal mechanism linking operational efficiency, environmental performance, and educational functions within Waste-to-Energy facilities. This study contributes a transferable architectural framework that advances the discourse on sustainable industrial architecture while providing practical guidance for the planning and design of future Sustainable Waste Management Education Facilities supporting circular economy principles and sustainable urban development.